Francesca Woodman: Photography beyond the limits of representation - Pereira, Bruno [UNESP]; Filho, Fernando Silva Teixeira [UNESP] (Universidade Estadual de Londrina, 2017)
This paper intends to combine the relationship between photography and art, through the photographic work of American photographer Francesca Woodman (1958-1981). The anal-ysis parameter will focus on Woodman's contribution to the discussions about photography as a medium, in particular, issues concerning the representation, thus, we seek to demonstrate how Woodman questioned the precepts of photography of her time and presented clues for the con-struction of a photographic language resulting from the inventive power of the artist's creative process in her relation to photography.
Francesca Woodman: A fotografia para além dos limites da representação
Keywords: Art; Francesca Woodman; Photography; Representation